Adherencia al Protocolo de Higiene de Manos. Servicio de Neonatología. Hospital Provincial General Docente Riobamba. Abril-agosto 2018. - Deisy Viviana, Cayambe Acan (2018)
The present project is joined to the hand hygiene protocol in the neonatology service of the Provincial General Teaching Hospital Riobamba, is a qualitative, descriptive study of cross-sectional nature; joined to the hand hygiene protocol by health personnel. This protocol is fundamental and of utmost importance, especially before carrying out cleaning procedures. The universe consisted of 36 people and the sample was made up of 30 people, 18 nurses, 6 nursing and medical interns, and 6 doctors, with exclusion criteria those people who were not present during the obtaining of the data. There were two instruments applied a survey that helped to identify knowledge about hand hygiene, and an observation guide based on the moments and steps of hand hygiene, which evidenced compliance with the protocol by health personnel. The results, in a general approach to knowledge, indicated that 53% responded the survey correctly, on the other hand, in terms of compliance with the moments, it was 78%, and in the steps the compliance was 85%. The educational guide was designed based on the hand hygiene guide of the WHO and the hand washing manual of the Neonatology service of the Provincial General Teaching Hospital Riobamba